Negotiating with Modernity: Smooth but Selected Changes in the Benda Kerep Village of Cirebon in 1990-2010 - Nurul Rosidin, Didin; Ibrahim, Muhamad; Saefullah, Asep; Sa'dudin, Ihsan (Journal of Asian Social Science Research, 2024)
This paper examines the evolving dynamics within the traditional community of Benda Kerep, Cirebon, as they navigate the pressures of modernization. Employing a qualitative methodology with a descriptive-analytical approach grounded in historical perspective, the study undertakes the following steps: topic selection, heuristics (data collection), source criticism (verification), interpretation (data analysis), and historiography (writing). Findings reveal that the residents of Benda Kerep maintain a strong commitment to their ancestral teachings, customs, and traditions. However, since the 1990s, they have also selectively integrated modern ideas and technologies. For instance, they have embraced modern education systems alongside traditional pesantren-based learning and utilized contemporary technologies in their rituals and ceremonies, such as Muludan, Haulan, and Shawalan. This duality highlights their adaptive strategies in preserving cultural heritage while engaging with modernity.